Administration and gender sensitivity: challenges and suggestions - Singh, Bimal Deep (2005)
Administration or executive, legislature and judiciary are the power centers in any society and do not want to share authority with any one else. If women are not used to the `outside' world, bureaucracy is equally unused to deal with women, which can be a factor that can stand as an impediment in the way of women's empowerment. In India the executive is extremely powerful and yet the constitutional and legal provisions pertaining to women are not being properly executed. This shows an indifferent view of the administration towards the fair sex. There is only formal gender equality existing at present. We must have a re-look at our legal system and policymaking. Women can contribute a lot in fresh policy making and in correcting the existing one. However, it is also true that men are not going to part with their authority on their own. If women are empowered the bureaucracy will also have to get used to more of them. There are various methods contemplated by which these stereotype roles can be punctured, if not broken completely. With this in view, this paper will focus on issues such as, reservations as a device for gender justice, gender discrimination under structural reforms, training and improvement of existing training programs. - Reproduced.
Keywords: Civil service; Women in the civil service